Comparison of analytical and numerical solutions for the multigroup diffusion theory analysis of circulating fuel reactors - Ozgener, H. Atilla; Ozgener, Bilge (Elsevier BV, 2019)
Abstract We have developed analytical solutions for the multigroup diffusion theory analysis of circulating fuel reactors. The analytical solutions encompass both the criticality searches and the subcritical, source-driven cases. By comparing the analytical results with those of our in-house finite difference code, both the analytical and the numerical solutions are verified. By studying the variation of certain global parameters, like the effective multiplication constant, the subcritical multiplication constant (in the subcritical, source-driven cases) and the effective delayed neutron fraction, we tried to assess the general behavior of circulating fuel systems. The developed analytical solutions provide a useful tool for the verification of numerical methods developed for the neutronic analysis of circulating fuel systems of both the critical and subcritical, source-driven variety.